The role of platelet mediated thromboinflammation in acute liver injury - Morris, Sean M.; Chauhan, Abhishek (Frontiers in Immunology, 2022)
Acute liver injuries have wide and varied aetiologies and they occur both in patients with and without pre-existent chronic liver disease. Whilst the pathophysiogical mechanisms remain distinct, both acute and acute-on-chronic liver injury are typified by deranged serum transaminase levels and if severe or persistent can result in liver failure manifest by a combination of jaundice, coagulopathy and encephalopathy. It is well established that platelets exhibit diverse functions as immune cells and are active participants in inflammation through processes including immunothrombosis or thromboinflammation. Growing evidence suggests platelets play a dualistic role in liver inflammation, shaping the immune response through direct interactions and release of soluble mediators modulating function of liver sinusoidal endothelial cells, stromal cells and migrating and tissue-resident leucocytes. Elucidating the pathways involved in initiation, propagation and resolution of the immune response are of interest to identify therapeutic targets. In this review the provocative role of platelets is outlined, highlighting beneficial and detrimental effects in a spatial, temporal and disease-specific manner.